2016
DOI: 10.1186/s12889-016-3380-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of women initiating ART during pregnancy versus breastfeeding in Option B+ in Malawi

Abstract: BackgroundMalawi adopted the PMTCT strategy ‘Option B+’ in 2011, providing life-long ART for all HIV-infected pregnant and breastfeeding women. We explored differences in characteristics and outcomes of women initiating ART during pregnancy versus breastfeeding.MethodsWe conducted a retrospective cohort analysis of women in Zomba District, southern Malawi, from January 2012- September 2013. Data were extracted from the Zomba District Observational Cohort Study, a surveillance project collecting data from stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
(14 reference statements)
4
14
2
Order By: Relevance
“…The current study includes the recent year data at which most strategies as a country level were implemented to decrease LTFU like bringing services closer to communities by expanding ART sites to above 1,500 Health facilities, increasing service provision by expanding trained health personnel in order to decrease waiting times at the facility than the previous study(2013, 2014 and 2015).The variation could also be explained by the difference in study setting, since this study was conducted at one referral hospital whereas, a study conducted in Northeast Ethiopia was done in four hospital and ten health centers. Studies showed that magnitude of lost to follow up varied according to level of health institutions (23,29). Moreover, the lower incidence of LTFU in the current study might be due to the fact that different programs/measures were implemented in the country in recent years to decrease the rate of LTFU among HIV infected women.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The current study includes the recent year data at which most strategies as a country level were implemented to decrease LTFU like bringing services closer to communities by expanding ART sites to above 1,500 Health facilities, increasing service provision by expanding trained health personnel in order to decrease waiting times at the facility than the previous study(2013, 2014 and 2015).The variation could also be explained by the difference in study setting, since this study was conducted at one referral hospital whereas, a study conducted in Northeast Ethiopia was done in four hospital and ten health centers. Studies showed that magnitude of lost to follow up varied according to level of health institutions (23,29). Moreover, the lower incidence of LTFU in the current study might be due to the fact that different programs/measures were implemented in the country in recent years to decrease the rate of LTFU among HIV infected women.…”
Section: Discussionmentioning
confidence: 67%
“…Various literatures reported that LTFU can be affected by various factors, including socio-demographic and economics, behavioral and clinical variables. Reports from Africa indicated that, maternal age less than 25 years (12,13,15,21,26,27,32), less than 26 years (33), and less than 30 (23) were statistically signi cant positive predictor for LTFU. Moreover, Educational status (15,28), Marital status (19), unemployment status (34), number of pregnancies (13), religious reasons, and partner HIV status (12,16) were a signi cant predictor for LTFU.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our study supports others in suggesting that being younger at ART initiation reduces retention in care. 11,[17][18][19] Several factors may contribute to poor retention among younger women, including reduced readiness for ART, decreased knowledge of the benefits of PMTCT, as well as stronger feelings of internalised and perceived stigma. 20,21 Older women may have more social support within partnerships and families which allow them to better manage ART.…”
Section: Discussionmentioning
confidence: 99%